Nutritional assessment and support - Grant, Anne (S. DeHoog, 1991)
This book provides the clinician with practical guidelines to identify, evaluate, and treat these patients. This is a step-by-step guide instructing healthcare providers with proper metabolic medicine protocols. This book bridges the gap of knowledge in the field of metabolic medicine and clinical nutrition among practicing physicians.